Self-Powered Active Vibration Control: Concept, Modeling, and Testing - Jin-Yang Li; Songye Zhu (Engineering, 2022)
Despite their superior control performance, active vibration control techniques cannot be widely used in some engineering fields because of their substantial power demand in controlling large-scale structures. As an innovative solution to this problem, an unprecedented self-powered active vibration control system was developped in this study. The topological design, working mechanism, and power flow of the proposed system are presented herein. The self-powering ability of the system was confirmed based on a detailed power flow analysis of vibration control processes. A self-powered actively controlled actuator was designed and applied to a scaled active vibration isolation table. The feasibility and effectiveness of the innovative system were successfully validated through a series of analytical, numerical, and experimental investigations. The setup and control strategy of the proposed system can be readily extended to diversified active vibration control applications in various engineering fields.